The role of ICDS services on early childhood development: A cross-sectional study in Hyderabad, Telangana - Sai Sreeharshita Malla; Nanda Kishore Kannuri; Varun Agiwal; AY Nirupama; Hira Pant Ballabh (Journal of Family Medicine and Primary Care, 2024)
Background: Integrated child development services (ICDS) include supplementary nutrition, nutrition and health education, health check-ups, immunization, preschool education, and referral services targeted at beneficiaries including pregnant and lactating mothers, children below six years, and women of reproductive age. Specific interventions are implemented to support children for a higher developmental outcome. Objectives: The aims of this study are (1) to compare the development of ICDS beneficiaries in the age group of 4–6 years with the dropouts, (2) to assess caregiver practices among mothers of beneficiaries and the dropouts, and (3) to understand the perceptions of Anganwadi workers (AWWs) on early child development (ECD) and ICDS services. Methods: A cross-sectional study was conducted for two months in select Anganwadi centers (AWCs) of Hyderabad. AWCs were selected through multi-stage sampling. Respondents included 114 mothers and five AWWs. Quantitative data was collected by a questionnaire and qualitative data through an interview guide. Proportions were estimated for description. STATA 14.0 was used to find out correlates of development in children through unpaired t-test, Chi-square test, and logistic regression. Thematic analysis was done for qualitative data. Results: About 68.42% and 33.33% of children from the beneficiary group were found to show normal cognitive and emotional development when compared to the dropout group (59.65% and 21.05%, respectively). KAP assessment revealed no significant difference between the mothers of dropouts and beneficiaries. Lack of infrastructure and poor attention to preschool activities were identified as reasons for dropout. Conclusion: Improving infrastructure, capacity building of AWWs, and reducing their workload will help in focusing on ECD-related activities at ICDS centers.